(untitled) (City Dental College Journal, 2018)
Background: After a total glossectomy, one lost the ability to speak and swallow due to the loss of tongue mobility and the increase of space between the palate and tongue remnants. To improve swallowing by creating negative pressure, tongue and palatal drop prostheses can be utilized. This prosthesis does not restore other tongue functions such as mastication, speech articulation and resonance because the prosthesis cannot reproduce natural tongue movements. Purpose: To rehabilitate the tongue deformity due to the gun shot wound. Methods and Materials: The case report revealed the total lost of tongue of a Bangladeshi patient who cannot be able to swallow and speak. The remaining teeth still fully intact but the palatal drop and tongue prosthesis was fabricated with the silicone prosthesis. Results: Both palatal drop prosthesis and tongue prosthesis allowed the patient to increase the capacity to swallow and reduce the remaining odondus space. The speech appeared to be more intelligiable but cannot fully restore. Conclusion: The quality of life of a patient after post operative follow-up appeared to be better; however, the physiologic function of the missing organ cannot fully restored. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13828 City Dent. Coll. J Volume-10, Number-1, January-2013 Retracted: Due to complain